Tools for stakeholder interaction and adaptation of business processes in the modern business environment - Podoinitsyn, S.; Stetsenko, S. (Ways to Improve Construction Efficiency, 2023)
In the modern world, interaction between stakeholders is an integral part of business. It allows for the achievement of common goals and ensures the sustainability of enterprise development. However, stakeholder interaction is not always easy and seamless. Sometimes it can face obstacles that arise from different interests and views on business development. It is important to note that interaction between stakeholders should be based on mutual trust and understanding. In this way, companies can ensure effective interaction and achieve common goals. To do this, it is necessary to take into account the interests of all stakeholders and ensure mutual benefit in the interaction. One approach to achieving common goals is to consider stakeholder interaction as the adaptation of business processes in new realities. Digitalization of business processes can help companies be more efficient and competitive. For example, the use of cloud technologies allows for the storage and processing of large amounts of data, which facilitates decision-making processes and ensures a quick response to changes in the internal and external environment. Business process reengineering involves a complete review and transformation of business processes in order to achieve better results. This can be useful for companies facing complex stakeholder interaction problems. For example, reviewing the communication process with customers can help provide better service and meet customer needs. The result of stakeholder interaction and changes to existing business processes may be the replacement of internally developed algorithms with entirely new steps or the modernization of stakeholder interaction processes. Adding important elements that allow for the management of other stakeholders’ interests can provide expected but higher quality results. Therefore, stakeholder interaction is a key factor in business success. Considering this issue from the perspective of adapting business processes to new realities, their digitalization, and reengineering can help companies achieve common goals and ensure sustainable development. This is important not only for the company itself but also for the entire business environment, which must be stable and progressive for success.